2010
DOI: 10.1109/tkde.2009.85
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Framework for Providing Recommendations in Social Tagging Systems Based on Ternary Semantic Analysis

Abstract: Social Tagging is the process by which many users add metadata in the form of keywords, to annotate and categorize items (songs, pictures, web links, products, etc.). Social tagging systems (STSs) can provide three different types of recommendations: They can recommend 1) tags to users, based on what tags other users have used for the same items, 2) items to users, based on tags they have in common with other similar users, and 3) users with common social interest, based on common tags on similar items. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 36 publications
0
95
0
1
Order By: Relevance
“…This model was chosen as it performed the best in the comparative study presented in the Section 4. Details of the remaining techniques that were used in the study could be found in [2,[23][24][25][26][27][28][29][30][31]. The experiments have been performed to analyze the suitability of RTF technique for applying tag-based recommendations in e-learning environments as well as comparing graph-based and tensor based approaches for tag recommendation applied to e-learning environments.…”
Section: Applying Tag-based Recommender Systems To E-learning Environmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was chosen as it performed the best in the comparative study presented in the Section 4. Details of the remaining techniques that were used in the study could be found in [2,[23][24][25][26][27][28][29][30][31]. The experiments have been performed to analyze the suitability of RTF technique for applying tag-based recommendations in e-learning environments as well as comparing graph-based and tensor based approaches for tag recommendation applied to e-learning environments.…”
Section: Applying Tag-based Recommender Systems To E-learning Environmentioning
confidence: 99%
“…Since there is no straightforward way to find the optimal values for c1, c2 and c3, we follow the technique presented by [30] that a 70% of the original diagonals of X(1), X(2) and X(3) matrices can give good approximations. Thus, c1, c2 and c3 are set to be the numbers of singular values by preserving 70% of the original diagonals of X(1), X(2) and X(3) respectively in each run.…”
Section: Higher Order Singular Value Decomposition (Hosvd) Algorithmmentioning
confidence: 99%
“…Panagiotis Symeonidis et al [20] developed a unified framework to model the three types of entities that exist in a social tagging system: users, items and tags. These data are represented by a 3-order tensor on which latent semantic analysis and dimensionality reduction is performed using higher order singular value decomposition technique.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The collaborative labeling schemes are supposed to gather information from the public and the quality of information users can acquire will augment as the magnitude of data people supplied expands [19]. At present, the Internet's numerous collaborative labeling sites are in existence, but there is the requirement for a service to incorporate the data from the manifold sites, to build a huge and compact set of collaborative data, from which users can have more precise and richer updates than from a particular site.…”
Section: Co-published By Atlantis Press and Taylor And Francismentioning
confidence: 99%
“…In this section, some of the earlier works related to collaborative labeling of web pages for easy searching and recommendation to new users are discussed briefly. Panagiotis Symeonidis et al [19] developed an integrated framework to model the three categories of entities that existed in a social tagging system: users, items, and tags. A lot of users insert metadata in the form of keywords, to interpret and classify items (songs, pictures, web links, products, etc).…”
Section: Review Of Related Workmentioning
confidence: 99%